Chromaticity, antioxidant, and antimicrobial activity of lutein and β-carotene from local pumpkin and sweet potato - Ainaa Eliah binti Abu Bakar
Carotenoids are coloured Carotenoids are coloured pigments that found in nature which have their specific colour range of yellow, orange and red colours. Colour plays an important role to make sure the products are attractive to the consumers. The natural colorant is colouring that can be obtained from natural sources such as plants, vegetables, animals and minerals. This study established that the working scheme via open column chromatography (OCC) established from pumpkin and sweet potato demonstrated that isolation of the β-carotene and lutein pigment were successful with 97.2% and 95.46% purity with the coefficient of correlation of 0.9961 and 0.9959 respectively. The β-carotene extract has presented strong activity on DPPH scavenging radicals with the percentage of inhibition at 99.45% in 0.008 mg/ml concentration as compared to lutein, which contributed 65.6% at 0.5mg/ml. As for antimicrobial activity, a positive result for both β-carotene and lutein pigment for bacterial and fungal species except for Tricho sp. In this study, the results from chromaticity stability of PLA-β-carotene and lutein coating from 1mg/ml up to 3mg/ml treated with different pH value from 3.0 to 11.0, as well as the time of exposure from day 1 until day 15 revealed that there is no stable relationship between pH, yellow colour concentration and period of time in response to light. Marked differences were observed for PLA-β-carotene coating treated with different concentration of NaCl for 1 and 2 mg/ml concentration of carotenoid pigment for a period of time of 10 days and PLA-lutein coating treated with different temperature from -25°C to 50°C when exposed for 6 hours. In term of light exposure, PLA-β-carotene coating with lower concentration and PLA-lutein with higher concentration were found to slow the degradation process. In conclusion, this data suggests that although different carotenoid pigment concentrations had influenced chromaticity stability, light and time also affected pigment colour difference.